Implementation of Servant Leadership in Educational Institutions - Sinjaya, Andi; Lengkong, Indira Krisanti; Hafidhah, Hafidhah; Sari, Eliana; Karnati, Neti (Jurnal Edusci, 2024)
The purpose of this study is to describe how the implementation of servant leadership in educational institutions is implemented. This study uses a literature study method by reading, writing, analyzing, and summarizing. The data sources used are literature sources, namely books and journals related to research topics. The data analysis technique uses content analysis. Content analysis is used to research the most relevant, relevant, and quite relevant literature. Then, a study was carried out by looking at the year of publication from the most up-to-date, up-to-date, to not up-to-date but having substance related to this research. Then the researcher reads the abstract which will then be researched and recorded in detail by the researcher. The result of this study is that servant leadership can have a positive impact on educational institutions, namely increasing the creativity, innovation of subordinates, competence, and commitment to educational institutions. Servant leadership is a leadership model that can help educational institutions improve the quality achieved.